A prospective observational study of the incidence, natural history, and risk factors for intravenous immunoglobulin‐mediated hemolysis. Issue 4 (12th January 2021) - Pendergrast, Jacob; Armali, Chantal; Callum, Jeannie; Cserti‐Gazdewich, Christine; Jiwajee, Aziz; Lieberman, Lani; Lau, Wendy; Lin, Yulia; Parmar, Nagina; Pavenski, Katerina; Riden, Lorna Sampson; Shehata, Nadine; et al.
Abstract: Background: Intravenous Immune Globulin (IVIG) is used to treat numerous immune‐mediated and inflammatory conditions. There is growing awareness of hemolysis, occasionally severe, as a side‐effect of this therapy. While most cases are associated with anti‐A and/or anti‐B isoagglutinins, the frequency and mechanism of hemolysis remain poorly characterized. Study Design and Methods: A prospective observational study was conducted to determine incidence, natural history and risk factors for IVIG‐mediated hemolysis. A total of 99 infusions of high‐dose IVIG (2 g/kg or higher) administered to 78 non‐group O patients were monitored and graded according to Canadian IVIG Hemolysis Pharmacovigilance Group. Serum ferritin and C3/C4 levels were monitored as indicators of macrophage activation and complement consumption, respectively. Supplementary investigations included assessment for ABO zygosity, Secretor status, FcR polymorphisms, eluate IgG subclass, monocyte monolayer assay, and a panel of cytokines. Results: Hemolysis was observed in 32 of 99 (32%) of infusions, with 19 of 99 (19%) grade 2 or higher. Hemolysis was only apparent 5‐10 days after a completed IVIG infusion in 84% of cases and was associated with increases in serum ferritin without complement‐consumption. In univariate analysis, increased risk was observed in group AB patients, first‐time IVIG recipients, those not taking immuosuppressive medications, or patients treated with a specific IVIG brand; however, in multivariate analysis, product association was no longer observed. No other patient‐ or practice‐related risk factors were identified. Conclusion: IVIG‐mediated hemolysis is common and frequently severe. Monitoring for 5‐10 days following an infusion should be considered in non‐O patients receiving high‐dose IVIG with known risk factors. Abstract : See editorial on page 993–995,  in this issue